Interplay between lysine methylation and Cdk phosphorylation in growth control by the retinoblastoma protein. - Carr, S; Munro, S; Kessler, B; Oppermann, U; La Thangue, N (2011)
As a critical target for cyclin-dependent kinases (Cdks), the retinoblastoma tumour suppressor protein (pRb) controls early cell cycle progression. We report here a new type of regulation that influences Cdk recognition and phosphorylation of substrate proteins, mediated through the targeted methylation of a critical lysine residue in the Cdk substrate recognition site. In pRb, lysine (K) 810 represents the essential and conserved basic residue (SPXK) required for cyclin/Cdk recognition and phosphorylation. Methylation of K810 by the methyltransferase Set7/9 impedes binding of Cdk and thereby prevents subsequent phosphorylation of the associated serine (S) residue, retaining pRb in the hypophosphorylated growth-suppressing state. Methylation of K810 is under DNA damage control, and methylated K810 impacts on phosphorylation at sites throughout the pRb protein. Set7/9 is required for efficient cell cycle arrest, and significantly, a mutant derivative of pRb that cannot be methylated at K810 exhibits compromised cell cycle arrest. Thus, the regulation of phosphorylation by Cdks reflects the combined interplay with methylation events, and more generally the targeted methylation of a lysine residue within a Cdk-consensus site in pRb represents an important point of control in cell cycle progression.